Physical literacy in the field of physical education——A challenge and a possibility - Lundvall, Suzanne (Journal of sport and health science, 2015)
Publications of articles with physical literacy as a topic have increased dramatically since the beginning of 2000 s. The aim of this paper is to,through an explorative literature overview with an inductive approach, analyze frequent, and significant themes in published peer reviewed articles,with a focus on physical literacy. The database EBSCO has been used with the identifiers “physical literacy” and “physical literacy and evidence”.Furthermore ICSSPE Bulletin＇s special issue on physical literacy has been included in the overview. The findings have resulted in three key themes： assumptions of the concept physical literacy and its educative role, sports development and physical literacy, and assessment and physical literacy. Future studies are needed to examine if the advocated pedagogical strategies based on the concept physical literacy have led to a reorganized and revitalized school subject. There is also an existing critique towards making physical literacy an idealistic neutral concept or synonym with fundamental movement skills or sports talent identification. The role of higher education emerges as crucial for the next step of the development of the scientific framework as this involves how physical literacy will be socially configured, nurtured, and embodied in practice.Copyright ó 2015, Shanghai University of Sport. Production and hosting by Elsevier B.V. All rights reserved.